Comparative Chemical and Mineral Characterization of Paleocene Coal of Sonda Coalfield, Sindh, Pakistan - Imdadullah Siddiqui; Abdul Salam Soomro; Muhammad Hassan Agheem (Mehran University Research Journal of Engineering and Technology, 2013)
The Sonda coalfield is located in the 125 km east of Karachi covering an area of about 1400 sq. km. Sonda coal was deposited in the Bara Formation, this Formation contains two main coal-bearing horizons; one is in the upper part and the second is lower part, which is recognized as Jheruck coal zone. In the Bara Formation, coal at Sonda was deposited in three main horizons, named as Daduri, Sonda and Jherruck coal zone. The coal was deposited in in Paleocene age. Sonda coal is enriched with Zn, Ni and Pb. Present mineralogical study shows that Sonda coal contains calcite, dolomite, kaolinite and quartz. The comparison with US and Chinese coal values indicates that among all the analyzed elements, only Ni has high geometric values in Sonda than Chinese coal. GM (Geometric Mean) concentration for Al is higher in Sonda coal than US and Chinese coal values. Clarke values comparison shows that according to Zoller formula all elements in Sonda coal are depleting.